2022
DOI: 10.1186/s11658-022-00384-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of macrophage subtypes and exosomes in immunomodulation

Abstract: Macrophages are influential members of the innate immune system that can be reversibly polarized by different microenvironment signals. Cell polarization leads to a wide range of features, involving the migration, development, and organization of the cells. There is mounting evidence that macrophage polarization plays a key role in the initiation and development of a wide range of diseases. This study aims to give an overview of macrophage polarization, their different subtypes, and the importance of alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(46 citation statements)
references
References 143 publications
0
46
0
Order By: Relevance
“…They have been considered in recent years as ideal vesicles for future biologic therapies and have demonstrated their role and potential in the repair of damage in a variety of organ systems [23,[45][46][47]. Exosomes are EVs with a size range of 40-160 nm (average ~ 100 nm) in diameter and exert their regulatory effects mainly through their inclusions, such as proteins, miRNAs, and long noncoding RNAs [48][49][50]. Of these, miRNAs are currently considered the most diverse.…”
Section: Discussionmentioning
confidence: 99%
“…They have been considered in recent years as ideal vesicles for future biologic therapies and have demonstrated their role and potential in the repair of damage in a variety of organ systems [23,[45][46][47]. Exosomes are EVs with a size range of 40-160 nm (average ~ 100 nm) in diameter and exert their regulatory effects mainly through their inclusions, such as proteins, miRNAs, and long noncoding RNAs [48][49][50]. Of these, miRNAs are currently considered the most diverse.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they can merge with the plasma membranes of target cells [ 41 , 42 ]. MSCs are multipotent, ubiquitous cells that can differentiate into various mesodermal germ layer cell types [ 13 , 40 , 43 , 44 , 45 ]. MSCs have two fundamental properties: (i) they are immunomodulatory; hence, they can decrease the levels of cytokines such as interleukin 1 beta (IL-1β) and tumor necrosis factor-alpha (TNF-α) while boosting the levels of transforming growth factor beta (TGF-β); and (ii) they have a strong regeneration capacity [ 26 ].…”
Section: Mesenchymal Stem Cell-derived Exosomesmentioning
confidence: 99%
“…For instance, macrophages and reticuloendothelial cells can directly or indirectly eliminate liposomes. Moreover, multiple investigations have demonstrated that exosomes avoid the immune system and prolong circulation time [ 11 , 12 , 13 ]. Nucleic acids (DNA, ribonucleic acid, micro-RNAs, and long noncoding RNAs (lncRNAs)), lipids, metabolites, proteins, cytosolic proteins, glycoconjugates, amino acids, and membrane proteins are embedded in exosomes ( Figure 1 A).…”
Section: Introductionmentioning
confidence: 99%
“…The approaches that change the balance of macrophage phenotypes seem effective through dynamic regulation of immune systems [ 85 , 86 ]. As shown above, exosomes are a useful tool to regulate macrophage polarization in tumor cells, and then in current years, anticancer effects through the regulation of macrophage polarization by exosomes have been investigated [ 104 ] ( Table 2 ). Cervical cancer is the fourth most common cancer among women worldwide and is difficult to diagnose in the early stage, where miR-423-3p was suggested as a potential modulator of the cancer progression.…”
Section: Exosome-induced Macrophage Polarization In Cancersmentioning
confidence: 99%